Adaptation Of The Subjective Happiness Scale Using The Confirmatory Factor Analysis (Cfa) Method - Awang ringko; Syarifah Hanim; Dini Dwinanda Putri; Rosa Akhirunnisa; Dira Utami, Anwar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Subjective happiness is an important psychological construct that influences individual well-being comprehensively. This study aims to adapt the Subjective Happiness Scale into Indonesian and examine its construct validity and reliability using Confirmatory Factor Analysis method. Research participants involved 220 university students from various higher education institutions in Indonesia with age range 18-25 years selected through convenience sampling. The adaptation process was conducted systematically through forward translation, back translation, profesional judgement, and cognitive interview stages to ensure semantic, conceptual, and cultural equivalence. The adapted instrument consists of four items measuring individual global happiness using seven-point Likert scale. Analysis results showed satisfactory reliability with Cronbach's Alpha coefficient of 0.715 and all items had item-total correlation ranging from 0,781-0,947. CFA analysis confirmed unidimensional structure with excellent goodness of fit indices after model modification, namely CFI = 0.998, RMSEA = 0.030, and SRMR = 0.017. All items had significant factor loadings ranging from 0,781-0,947 with t-values above 1.96, indicating strong validity. No items were eliminated as all items met the required psychometric criteria. These findings confirm that the Indonesian version of Subjective Happiness Scale has robust psychometric properties and can be used as a valid, reliable, and efficient instrument for measuring subjective happiness for various research purposes and practical applications in Indonesian context.